“We [teachers] first require basic technical [skills] training”: Investigating formal professional development pathways and knowledge needs of teachers for technology integration - Abedi, Emmanuel Ayisi (Education and information technologies, 2024)
Internationally and in Ghana, formal professional development is cited in many education policies as a focal lever for transforming pedagogy and engaging students in cognitively demanding learning processes with digital technologies. Yet, this expectation for technology integration has proven difficult to achieve for many teachers, often due to the nature of technology professional development programs, which in Ghana, have received limited research attention. In response, this qualitative study, based on interviews with 20 teachers, five education officials, and five headteachers, investigated formal technology professional development opportunities in Ghana, including teachers’ knowledge needs and preferred training subject. Thematic analysis revealed the existence of professional learning communities, district-private partnership workshops, curriculum reform workshops, and cluster-based professional development programs. These in-service training avenues all prioritise equipping teachers with basic technical skills to use technologies as productivity tools. Teachers strongly prefer these skill sets, considering them prerequisites for supporting routine teacher-centred teaching tasks. Findings reveal that most professional development programs and teachers tend to overlook pedagogical transformation and innovation aspects of integrating technology. The study argues that technology professional development should shift from emphasising isolated technical skills training to equally prioritising pedagogical knowledge development for teachers to effectively facilitate student-centred learning and teaching with digital technologies.